Empowering pilgrims through digital literacy: Evaluating ritual understanding via mobile hajj applications at KBIHU Ahmad Dahlan - Aris Rakhmadi; Susilo Hartono; Muchlas Muchlas; Anton Yudhana (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2026)
This community service initiative evaluates the impact of mobile applications, namely Haji Pintar–Satu Haji and Kawal Haji, in enhancing digital literacy and ritual understanding among pilgrims at KBIHU Ahmad Dahlan, Pringsewu. The program was implemented over a one-month period and involved participants engaging in mobile-based tutorials and mentoring activities designed to support comprehensive Hajj preparation. The learning materials focused on improving participants’ understanding of Hajj rituals while simultaneously strengthening their ability to use digital applications effectively. Survey results indicated that nearly all participants had access to Android smartphones, with 41.3% of respondents assessing their digital skills as “very good.” Among the available features, video tutorials were the most frequently accessed, accounting for 34.8% of usage, as they were perceived as clear and easy to understand. The majority of pilgrims reported improved comprehension of Hajj rituals after participating in the program. Despite these positive outcomes, several challenges were identified, including infrequent application usage, accessibility limitations for some users, and participant requests for offline learning content. Overall, the findings demonstrate the significant potential of mobile applications to support Hajj preparation through religious education and digital engagement. The study recommends further development through more inclusive application design, offline accessibility, and sustained digital engagement strategies to enhance the effectiveness of community outreach programs in religious education.